PENGARUH PENGGUNAAN BERBAGAI JENIS MULSA TERHADAP PRODUKSI BAWANG MERAH (Allium cepa L. Var. Agregatum) - Use Etica; Ahmad Husaini (UPN VETERAN JAWA TIMUR, 2019)
This study aimed to determine the effect of the use of black silver plastic, eucalyptus leaf, and palm sugar fibers on shallot production and to know the comparison of shallot plant growth response in the use of black silver plastic, eucalyptus leaf and palm sugar fibers. The treatment includes black silver plastic, eucalyptus leaf, palm fibers mulch, and control (no mulch). Observation of variables included plant height, leaf number, weight of the sample plant, weight of crop harvest samples, weight of tuber crops, and number of tubers. Plant observations were carried out at 7, 14, 21, 28, 35, 42, 49, and 56 days after planting. Observation data were analyzed by using analysis of varians (ANOVA) and after that followed by Duncan test level 5%. Treatment by using black silver plastic, eucalyptus leaf and palm sugar fibers gave a significant effect on plant height, leaf number, sample plant weight, sample crop weight, and tuber weight. The treatment using black silver plastic mulch gave the highest average effect of the results of observations of plant height, number of leaves, sample wet weight, weight of sample crop harvest, and tuber weight.